Englishization for Humor: Code-Mixing for Literary Creativity in Pakistani Languages - Muhammad Kamal Khan, Muhammad Nawaz (JSSH, 2023)
The Englishization of South Asian languages has been pursued by a number of leading scholars for the last more than fifty years (e.g., Kachru, 1969; Kachru, 1989; Snell, 1993; Hock, 2015, 2019 among others). Based on the bilingual interaction between English and regional languages, these scholars are more interested in theorizing ‘Englishization’ as a dominant consequence of this ‘contact’ and highlighting its various implications including code-mixing- the blending of two or more languages in a single stretch of speaking or writing. However, the present paper explores this bilingual contact between English and South Asian languages by highlighting ‘Englishization’ for the sake of ‘humorous implications’ in the poetic writing of three major Pakistani languages including Urdu, Pashto and Punjabi. As a sample, 15 poems of comic poetry (five from each language) are selected and qualitatively analyzed focusing on the borrowed items in terms of their code-mixing performances for literary creativity. Though used as a tool for comic relief, this analysis shows code-mixing as a common practice among these linguistic communities whereby the process of ‘Englishization’ is actively in progress, serving as a medium for social critique as well as the consequence of fascination for English lexical items for artistic creativity. Finally, this research concludes that English has now started performing a wide variety of functions in South Asian linguistic communities including providing sources for literary creativity and stock for comic poetry